Joseph B. Clearihue - portrait of twelve unidentified soldiers photograph - http://id.worldcat.org/fast/2011150 (1914)
A group portrait of twelve unidentified soldiers and officers in military uniform during World War I, possibly members of the 62nd Battery, 15th Brigade, Canadian Field Artillery prior to deployment.